Awangardowa cyberpoezja? - Alina Świeściak (Postscriptum Polonistyczne)
The article discusses cyberpoetry as a category of avantgarde writing. The author proves that cyberpoertry should not be regarded as modern avantgarde writing, because modern culture does not follow the avantgarde cultural and aesthetic norms (such as novelty, originality). The fact that cyberpoetry applies some avantgarde aesthetic tools (collage and montage) must be regarded as nonavantgarde continuation.